The Greater East Asia Co-Prosperity Sphere when total empire met total war - Yellen, Jeremy A. 1977- (Studies of the Weatherhead East Asian Institute, Columbia University, 2019)
"This book explores the Greater East Asia Co-Prosperity Sphere, Japan's ambitious wartime attempt to create a new order in East and Southeast Asia"--